1986
DOI: 10.1111/j.1365-2125.1986.tb05239.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette smoking on 7‐ethoxyresorufin O‐deethylase and other monooxygenase activities in human liver: analyses with monoclonal antibodies.

Abstract: 1 Four cytochrome P-450 enzyme activities, 7-ethoxyresorufin O-deethylase (ERDE), coumarin 7-hydroxylase (CH), 7-ethoxycoumarin 0-deethylase (ECDE) and aryl hydrocarbon hydroxylase (AHH) were measured in human liver needle biopsy samples from smokers and non-smokers. Cigarette smoking was verified and quantitated by measuring plasma cotinine levels.3 Enzyme inhibitory monoclonal antibodies (MAb) to a 3-methylcholanthrene-induced (MAb 1-7-1) and phenobarbitone-induced (MAb 2-66-3) rat hepatic cytochrome P-450 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
37
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 27 publications
13
37
0
Order By: Relevance
“…4A). 7-ER (Pelkonen et al, 1986;Rodrigues and Prough, 1991), a putative substrate for CYP1A1, inhibited the formation of 4-hydroxydebrisoquine in a concentration-dependent manner in microsomes expressing CYP1A1 (Fig. 4B).…”
Section: Resultsmentioning
confidence: 91%
“…4A). 7-ER (Pelkonen et al, 1986;Rodrigues and Prough, 1991), a putative substrate for CYP1A1, inhibited the formation of 4-hydroxydebrisoquine in a concentration-dependent manner in microsomes expressing CYP1A1 (Fig. 4B).…”
Section: Resultsmentioning
confidence: 91%
“…However, it has proved more difficult to demonstrate such an effect in vitro, with microsomal fractions from human liver. Differences in hepatic aryl hydrocarbon hydroxylaste activity (which is highly inducible in rat liver by PAH) between smokers and nonsmokers are low or non-existent (Boobis et al, 1980;Pelkonen et al, 1986). In contrast, the high affinity components of the O-deethylation of both phenacetin (Kahn et al, 1985) and 7-ethoxyresorufin (Pelkonen et al, 1986) are two to three-fold greater in liver samples from smokers than in those from non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke is a complex mixture of organic and inorganic compounds, and in animals it has inducing properties similar to PAH (Uotila et al, 1977;Conney, 1982Conney, , 1986. Whereas treatment of animals with PAH results in considerable elevation of hepatic aryl hydrocarbon hydroxylase activity, such a change has never been observed in man following cigarette smoking (Boobis et al, 1980;Pelkonen et al, 1986). However, cigarette smoking does cause a profound induction of phenacetin oxidation in man determined both in vivo and in vitro (Pantuck et al, 1972(Pantuck et al, , 1974Boobis et al, 1981;Kahn et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The final substrate we used, ethoxycoumarin, is metabolised (at least at high concentrations) substantially by isozyme(s) distinct from those responsible for the metabolism of ethoxyresorufin. Thus ethoxyresorufin metabolism, but not that of ethoxycoumarin, is inhibited by an antibody to a 3-MC-induced rat hepatic cytochrome P-450 and is also increased in the livers of cigarette smokers (Pelkonen et al, 1986). Ryan et al (1984) found that ethoxycoumarin was only poorly metabolised by purified rat cytochromes P-450, g and h. It is not clear what the major isozyme(s) responsible for ethoxycoumarin dealkylation are.…”
Section: Discussionmentioning
confidence: 99%